High-temperature-resistant electrostatic adsorption type automobile skylight sunshade curtain and preparation method thereof

The four-layer high-temperature resistant electrostatic adsorption skylight sunshade curtain solves the problems of inconvenient installation, easy detachment, and poor heat insulation of traditional sunshade curtains, achieving soft, stable adsorption and efficient heat insulation.

CN121340744APending Publication Date: 2026-01-16SHAOXING TRAVELLER HOUSEHOLD PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511719426.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-21
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Traditional car sunroof sunshades have problems such as inconvenient installation, lack of softness, easy detachment, and poor heat insulation.

Method used

The high-temperature resistant electrostatic adsorption sunshade features a four-layer structure, including a transparent PE electrostatic adsorption layer, a reflective heat insulation layer, a light-blocking adhesive layer, and an interior layer. It enhances thermal stability through electrostatic adsorption, a reflective silver layer, and a carbon fiber mesh, while combining suede fabric to improve softness and fit.

Benefits of technology

It achieves railless and rollerless installation, soft and stable adsorption, significant heat insulation effect, extremely high UV protection performance, strong multi-layer composite interface, and excellent protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121340744A_ABST
    Figure CN121340744A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant electrostatic adsorption type automobile sunroof sunshade curtain and a preparation method thereof, and belongs to the technical field of automobile sunroof sunshade curtains. The sunshade curtain comprises a transparent PE electrostatic adsorption layer, a reflective thermal insulation layer, a shading bonding layer and an inner decoration layer which are sequentially compounded from top to bottom. The transparent PE electrostatic adsorption layer is made of a polyethylene film through electrostatic treatment and is used for being adsorbed on the surface of skylight glass; the reflective thermal insulation layer comprises a polyurethane adhesive layer, a reflective silver layer arranged on the adhesive layer and a carbon fiber reinforced grid embedded in the adhesive layer; the shading bonding layer is formed by a hot melt adhesive dispersed with black shading master batches; and the inner decorative layer is made of suede fabric and is compounded with the reflective thermal insulation layer through the shading bonding layer. Through the design of a multi-layer composite structure, excellent heat insulation performance is achieved, and meanwhile the high-temperature-resistant, high-peel-strength and ultraviolet-proof functions are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of automotive sunroof sunshade technology, specifically a high-temperature resistant electrostatic adsorption sunroof sunshade and its preparation method, which is suitable for improving the sunshade and heat insulation performance of automotive sunroofs. Background Technology

[0002] With the increasing popularity of panoramic sunroofs in cars, sunshades have become an essential accessory for summer driving. Traditional or currently mainstream car sunroof sunshades typically have the following drawbacks: Traditional electric retractable sliding sunshades typically consist of a roller, a guide rail, and a curtain. The curtain is usually a single layer or a simple double-layer structure. The presence of the guide rail and roller makes installation inconvenient and requires professional auto mechanics to install, which increases costs. Sunshades that don't use roller tracks require clips, adhesive tape, or magnetic attachment for installation. Because sunshades use thicker fabrics (usually at least 5mm thick) to ensure sufficient light blocking and heat insulation, they are less flexible, leading to curling edges and a poor fit after installation. Clips or adhesive tape are prone to detaching after prolonged use and cannot be restored to a proper fit, while magnetic attachments are very easy to fall off while the vehicle is in motion. Therefore, there is an urgent need for a sunshade solution that combines high-efficiency heat insulation, good fit, high flexibility, and stable adhesion. Summary of the Invention

[0003] The first objective of this invention is to provide a high-temperature resistant electrostatic adsorption type skylight sunshade curtain, and the second objective is to provide a method for preparing the high-temperature resistant electrostatic adsorption type skylight sunshade curtain, so as to solve the problems mentioned in the background art.

[0004] To achieve the above objectives, the present invention provides the following technical solution: A high-temperature resistant electrostatic adsorption type car sunroof sunshade comprises the following four layers stacked from top to bottom: (a) Transparent PE electrostatic adsorption layer, made of polyethylene film through electrostatic treatment, used to adsorb onto the surface of the skylight glass; (b) A reflective heat insulation layer comprising a polyurethane adhesive layer, a reflective silver layer disposed on the adhesive layer, and a carbon fiber reinforced mesh embedded in the adhesive layer; (c) A light-shielding adhesive layer, consisting of a hot melt adhesive in which black light-shielding masterbatch is dispersed; (d) The interior layer is made of suede fabric and is composited with the light-blocking adhesive layer and the reflective heat insulation layer.

[0005] Furthermore, the thickness of the transparent PE electrostatic adsorption layer is 0.05-0.15 mm.

[0006] Furthermore, the reflective silver layer is a vacuum-plated aluminum layer with a thickness of 0.02-0.05 mm. The surface of the reflective silver layer is provided with longitudinal striped reflective bands, and the mesh density of the carbon fiber reinforced mesh is 20-30 mesh.

[0007] Furthermore, the velvet fabric of the interior layer is 0.1-0.2 mm thick.

[0008] Furthermore, the black light-shielding masterbatch contains carbon black and an infrared absorber, and the hot melt adhesive is a polyurethane reactive hot melt adhesive (PUR).

[0009] Furthermore, the thickness of the light-shielding adhesive layer is 0.15-0.3 mm, wherein the carbon black accounts for 15%-25% by mass, and the infrared absorber is ceramic micro powder, accounting for 5%-10% by mass.

[0010] A method for preparing the above-mentioned high-temperature resistant electrostatic adsorption type automotive sunroof sunshade includes the following steps: (i) A transparent PE film is corona treated and coated with an electrostatic liquid to form a transparent PE electrostatic adsorption layer; (ii) A carbon fiber mesh is laid on the surface of the reflective silver layer and laminated to the bottom of the transparent PE electrostatic adsorption layer using polyurethane adhesive; (iii) Apply polyurethane hot melt adhesive containing black light-blocking masterbatch to the base fabric to form a light-blocking adhesive layer; (iv) The composite obtained in step (ii) is bonded to the interior layer by a hot pressing process and then rolled to shape.

[0011] Furthermore, when the reflective heat insulation layer and the light-shielding adhesive layer are hot-pressed together, the temperature is controlled at 130-150℃ and the pressure is controlled at 0.8-1.2MPa.

[0012] Furthermore, the transparent PE electrostatic adsorption layer is prepared through the following modification process: S1: Corona treatment is performed on PE films with a thickness of 25-35μm. The treatment conditions are power of 8-12kW and film flow speed of 10-15m / min to improve surface energy and coating adhesion. S2: Coat the activated PE film surface with an electrostatic liquid containing quaternary ammonium salt (solid content 12-18%), controlling the coating amount to 1.2-2.0 g / m² to ensure uniform charge distribution; S3: Dry and cure the coated film in an oven at 80-100℃, and then roll it up to obtain the modified PE film.

[0013] Furthermore, the overall thickness of the sunshade is 0.32-0.8mm.

[0014] Compared with existing technologies, the advantages of this invention are as follows: High-temperature adhesion is achieved using a modified PE film, eliminating the need for clips, adhesives, and magnets, as well as rollers and guide rails; the carbon fiber mesh in the reflective silver layer of polyurethane adhesive enhances thermal stability, preventing reflectivity attenuation due to high-temperature deformation; black light-blocking masterbatch is uniformly dispersed in PUR hot melt adhesive, forming a continuous heat-absorbing barrier; suede is used to reduce glare inside the vehicle; the four-layer composite interface remains undelaminated after high-temperature pressing, ensuring the integrity of the thermal barrier. The overall thickness is not excessive, ensuring a smooth fit and preventing edge curling, while achieving significant heat insulation effects and extremely high UV protection efficiency, blocking almost all UV rays (over 99.95%), far exceeding the national standard for "Evaluation of Ultraviolet Protection Performance of Textiles," and providing almost complete blocking of long-wave ultraviolet (UVA) rays that cause skin photoaging. Attached Figure Description

[0015] Figure 1 This is a schematic diagram of the four-layer structure of the present invention; Figure 2 This is a schematic diagram of the reflective heat insulation layer.

[0016] In the picture: 1. Transparent PE electrostatic adsorption layer; 2. Reflective heat insulation layer; 21. Polyurethane adhesive layer; 22. Reflective silver layer; 23. Carbon fiber reinforced mesh; 3. Light-shielding adhesive layer; 4. Interior layer. Detailed Implementation

[0017] Example:

[0018] Please see Figure 1-2 A high-temperature resistant electrostatic adsorption type car sunroof sunshade includes the following four layers stacked from top to bottom: (a) Transparent PE electrostatic adsorption layer 1, made of polyethylene film by electrostatic treatment, is used to adsorb onto the surface of the skylight glass; (b) The reflective heat insulation layer 2 includes a polyurethane adhesive layer 21, a reflective silver layer 22 disposed on the adhesive layer, and a carbon fiber reinforced mesh 23 embedded in the adhesive layer; (c) The light-shielding adhesive layer 3 is composed of hot melt adhesive in which black light-shielding masterbatch is dispersed; (d) Interior layer 4 is made of suede fabric and is composited with the light-blocking adhesive layer and the reflective heat insulation layer.

[0019] Preparation Example 1:

[0020] Step 1: Electrostatic layer modification A 25μm thick polyethylene (PE) base film was subjected to corona treatment (power 8kW, film speed 10m / min), then coated with an electrostatic liquid containing quaternary ammonium salt (solid content 12%, coating amount 1.2g / m²), dried in an oven at 80℃ for 3 minutes, and then wound up to obtain a modified PE electrostatic adsorption layer.

[0021] Step 2: Composite of the reflective layer A 20-mesh carbon fiber mesh is laid on the surface of a vacuum-plated aluminum reflective silver layer (with longitudinal stripes, 1 mm wide and 4 mm apart), and polyurethane adhesive is evenly applied (coating amount 25 g / m²). The layer is then laminated under the electrostatic layer and cured at room temperature for 24 hours to form a reflective heat insulation layer.

[0022] Step 3: Applying the light-shielding layer Polyurethane reactive hot melt adhesive (PUR) is melted at 150°C and coated onto suede fabric (coating amount 35g / m²) to form a light-shielding adhesive layer containing 15% carbon black and 5% infrared absorber.

[0023] Step 4: Hot pressing Align the reflective / electrostatic composite with the light-shielding / interior composite, place them in a hot press (temperature 130℃, pressure 0.8MPa, time 20 seconds), roll them to set, and then wind them up.

[0024] Preparation Example 2:

[0025] Step 1: Electrostatic layer modification A 30μm thick polyethylene (PE) base film was subjected to corona treatment (power 8kW, film speed 10m / min), then coated with an electrostatic liquid containing quaternary ammonium salt (solid content 15%, coating amount 1.5g / m²), dried in an oven at 80℃ for 3 minutes, and then wound up to obtain a modified PE electrostatic adsorption layer.

[0026] Step 2: Composite of the reflective layer A 25-mesh carbon fiber mesh is laid on the surface of a vacuum-plated aluminum reflective silver layer (with longitudinal stripes, 1 mm wide and 4 mm apart), and polyurethane adhesive is evenly applied (coating amount 30 g / m²). The layer is then laminated under the electrostatic layer and cured at room temperature for 24 hours to form a reflective heat insulation layer.

[0027] Step 3: Laminating the light-shielding layer with the interior trim layer Polyurethane reactive hot melt adhesive (PUR) is melted at 150°C and coated onto suede fabric (coating amount 40g / m²) to form a light-shielding adhesive layer containing 20% ​​carbon black and 5% infrared absorber.

[0028] Step 4: Integral hot pressing molding Align the reflective / electrostatic composite with the light-shielding / interior composite, place them in a hot press (temperature 140℃, pressure 1.0MPa, time 30 seconds), roll them to set, and then wind them up.

[0029] Preparation Example 3:

[0030] Step 1: Electrostatic layer modification A 35μm thick polyethylene (PE) base film was subjected to corona treatment (power 8kW, film speed 10m / min), then coated with an electrostatic liquid containing quaternary ammonium salt (solid content 18%, coating amount 2.0g / m²), dried in an oven at 100℃ for 3 minutes, and then wound up to obtain a modified PE electrostatic adsorption layer.

[0031] Step 2: Composite of the reflective layer A 30-mesh carbon fiber mesh is laid on the surface of a vacuum-plated aluminum reflective silver layer (with longitudinal stripes, 0.5 mm wide and 3 mm apart), and polyurethane adhesive is evenly applied (coating amount 35 g / m²). The layer is then laminated under the electrostatic layer and cured at room temperature for 24 hours to form a reflective heat insulation layer.

[0032] Step 3: Applying the light-shielding layer Polyurethane reactive hot melt adhesive (PUR) is melted at 150°C and coated onto suede fabric (coating amount 45g / m²) to form a light-shielding adhesive layer containing 25% carbon black and 10% infrared absorber.

[0033] Step 4: Hot pressing Align the reflective / electrostatic composite with the light-shielding / interior composite, place them in a hot press (temperature 150℃, pressure 1.2MPa, time 40 seconds), roll them to set, and then wind them up.

[0034] Test Implementation Examples

[0035] The sunshade curtain samples obtained in Example 1 were tested according to GB / T 41560-2022 "Determination of heat-shielding properties of textiles", GB / T 18830-2009 "Evaluation of UV protection properties of textiles" and FZ / T 01010-2012 "Determination of peel strength of coatings on coated fabrics". The data are as follows: ; According to the report from the Shanghai Institute of Quality Inspection (W02592031261), the sample of this solution achieved a heat shading rate of 62.2% under the standard GB / T 41560-2022 "Determination of heat shading performance of textiles". In the actual simulation test, the temperature on the back of the material only increased from 21.2°C to 26.5°C within 30 minutes. The small temperature increase confirms that its heat insulation effect is significant and can effectively block solar radiation heat. The sample in this design has an ultraviolet protection factor (UPF) > 50 under the GB / T 18830-2009 standard "Evaluation of Ultraviolet Protection Performance of Textiles", with an actual measured average UPF > 2000. This indicates extremely high ultraviolet protection efficacy, blocking almost all ultraviolet rays (over 99.95%), far exceeding the national standard's entry threshold for "ultraviolet protection products" (UPF > 40), demonstrating exceptionally excellent protective performance. The average long-wave ultraviolet transmittance is 0.05%, far better than (lower than) the national standard requirement of 5%, and the UVA blocking rate is as high as 99.95%. It has almost complete blocking capability against long-wave ultraviolet (UVA) rays that cause skin photoaging, and its protective effect far exceeds the national standard, demonstrating outstanding performance.

[0036] The sample of this scheme was tested for peel strength (20.8 N in the longitudinal direction and 29.1 N in the transverse direction) under the standard FZ / T 01010-2012 "Determination of Peel Strength of Coated Fabrics", which shows that its multi-layer composite structure is firmly bonded and has good durability.

Claims

1. A high-temperature-resistant electrostatic adsorption type sunshade curtain for automobile sunroof, characterized in that, It comprises the following four layers which are compounded in sequence from top to bottom: (a) a transparent PE electrostatic adsorption layer (1) made of polyethylene film treated by electrostatic method, used for adsorption on the surface of sunroof glass; (b) a reflective heat insulation layer (2) comprising a polyurethane adhesive layer (21), a reflective silver layer (22) arranged on the adhesive layer, and a carbon fiber reinforced grid (23) embedded in the adhesive layer; (c) a light shielding adhesive layer (3) composed of hot melt adhesive with dispersed black light shielding masterbatch; (d) an interior layer (4) of suede fabric, compounded with the reflective heat insulation layer (2) through the light shielding adhesive layer (3).

2. The high temperature resistant electrostatic adsorption type sun visor curtain for automobile sunroof according to claim 1, characterized in that: The thickness of the transparent PE electrostatic adsorption layer (1) is 0.05-0.15mm; the suede fabric of the interior layer (4) is 0.1-0.2mm.

3. The high temperature resistant electrostatic adsorption type sun visor curtain for automobile sunroof according to claim 1, characterized in that: The reflective silver layer (22) is a vacuum aluminum plating layer with a thickness of 0.02-0.05mm, and the surface of the reflective silver layer (22) is provided with longitudinal stripe-shaped reflective strips, and the mesh density of the carbon fiber reinforced grid (23) is 20-30mesh.

4. The high temperature resistant electrostatic adsorption type sun visor curtain for automobile sunroof according to claim 1, characterized in that: The black light shielding masterbatch comprises carbon black and infrared absorber, and the hot melt adhesive is polyurethane reactive hot melt adhesive.

5. The high temperature resistant electrostatic adsorption type sun visor curtain for automobile sunroof according to claim 4, characterized in that: The thickness of the light shielding adhesive layer (3) is 0.15-0.3mm, wherein the mass percentage of carbon black is 15%-25%, and the infrared absorber is ceramic powder with a mass percentage of 5%-10%.

6. A method for making the high temperature resistant electrostatically dusterable sun visor for automotive window according to any one of claims 1-5, characterized in that: It comprises the following steps: (i) corona treatment on the surface of the transparent PE film and coating of electrostatic liquid to form the transparent PE electrostatic adsorption layer (1); (ii) laying the carbon fiber grid (23) on the surface of the reflective silver layer (22) and laminating it to the bottom of the transparent PE electrostatic adsorption layer (1) through the polyurethane adhesive (21); (iii) melting and coating the polyurethane hot melt adhesive containing black light shielding masterbatch on the base fabric (4) to form the light shielding adhesive layer (3); (iv) bonding the composite obtained in step (ii) with the interior layer (4) through the composite obtained in step (iii) by hot pressing process, and roll pressing and setting.

7. The method for preparing the high-temperature-resistant electrostatic adsorption type sun visor curtain for automobile sunroof according to claim 6, characterized in that: When the reflective heat insulation layer (2) and the light shielding adhesive layer (3) are compounded by hot pressing, the temperature is controlled at 130-150℃ and the pressure is 0.8-1.2MPa.

8. The method for preparing the high-temperature-resistant electrostatic adsorption type sun visor curtain for automobile sunroof according to claim 6, characterized in that: The transparent PE electrostatic adsorption layer (1) is prepared by the following modification process: S1: corona treatment on the PE film with a thickness of 25-35μm, the treatment conditions are power 8-12kW and film running speed 10-15m / min, to improve the surface energy and coating adhesion; S2: coating of electrostatic liquid containing quaternary ammonium salt on the surface of the activated PE film, controlling the coating amount to be 1.2-2.0g / m² to ensure uniform charge distribution; S3: drying and curing the coated film in an oven at 80-100℃, and winding to obtain the modified PE film.

9. The method for preparing the high-temperature-resistant electrostatic adsorption type sun visor curtain for automobile sunroof according to claim 8, characterized in that: In the S2 step, the solution solid content of the electrostatic liquid is 12-18%.

10. The high temperature resistant electrostatically dopped automotive sunroof shade curtain of claim 1, wherein, The overall thickness of the sunshade curtain is 0.32-0.8mm.